Assessing very advanced HIV disease in adolescent girls and young women - Naseem Cassim; Lindi-Marie Coetzee; Manuel P. da Silva; Deborah K. Glencross; Wendy S. Stevens (AOSIS, 2023)
Background: South Africa has the largest HIV epidemic globally, with ~7.5 million people living with HIV in 2021. Adolescent girls (AG) and young women (YW), aged 15-19 years and 20-24 years, are twice as likely to be living with HIV as their male counterparts. The national HIV prevalence for young women was 9.1% (2021), with limited data on disease severity. Objectives: This study assessed very advanced HIV disease (CD4 100 cells/μL) in adolescent girls and young women (AGYW) in South Africa. Method: A retrospective descriptive study analysed data collated from the National Health Laboratory Service database for 2017 to 2021 calendar years for AGYW. National and provincial specimen volumes, the percentage of tests with a CD4 100 cells/μL and ≥ 100 cells/μL, and the median and interquartile ranges, were calculated. Logistic regression determined the odds ratio for a CD4 100 cells/μL, controlling for age category. Results: Data for 1 199 010 CD4 specimens indicated a significant decrease in volumes of 34% from 287 410 (2017) to 189 533 (2021). The percentage of samples with a count 100 cells/μL ranged from 4.9% to 5.2% for YW versus 5.6% to 6.1% for AG. Provincial data for a CD4 count 100 cells/μL ranged between 4.5% and 8.3% in AG and 3.6% to 6.3% for YW. Logistic regression indicated a 24% higher likelihood for AG having a CD4 count 100 cells/μL. Conclusion: The study reported a higher proportion of very advanced HIV disease for AG versus YW nationally, with provincial disparity needing further analysis.